Application of Semantic Web Technologies in Requirements Engineering - Castañeda, Verónica (2010)
During the last years is increasing the interest in applying Semantic Web (SW) technologies in Requirements Engineering (RE). In this area, these technologies can be used to describe requirements specification documents, to formally represent requirements knowledge, or to formally represent domain knowledge. The purpose of this paper is to comprehensively review and present this knowledge area. The main contribution is the classification of approaches that include SW concepts within RE with the aim of clarifying the way in which the RE process can benefit from them. In addition, future trends are identified and described.